PENGEMBANGAN MEDIA KOMIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERUBAHAN ENERGI DI KELAS IV MADRASAH IBTIDAIYAH - Ihsan Rahmadi; Nirwana Anas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low conceptual understanding of fourth-grade students on energy transformation material at MIN 6 Medan, especially in the abilities of inferring, comparing, and explaining. This study aimed to develop a science comic learning media that is valid, practical, and effective in improving students’ conceptual understanding. This research used the Research and Development (R&D) method with the ADDIE model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 28 fourth-grade students of MIN 6 Medan. Data collection techniques were carried out through material and media expert validation sheets, teacher and student response questionnaires, as well as pre-test and post-test. The results showed that the comic learning media obtained a material expert validation percentage of 90% and a media expert validation percentage of 97.5% with the category of “Very Valid”. The practicality test results obtained a percentage of 96.43% from teachers and 92% from students with the category of “Very Practical”. In addition, the effectiveness test showed an average N-Gain score of 0.88 with a “High” category. Based on these results, the science comic learning media on energy transformation material was declared valid, practical, and effective in improving students’ conceptual understanding, especially in the abilities of inferring, comparing, and explaining.